한국 여성의 연령에 따른 피부 측정 데이터 기반 20대 ∼ 40대 피부 나이 예측 모형 개발 및 적용 - 맹지혜; Jihye Maeng; 남개원; Gaewon Nam (大韓化粧品學會誌, 2022)
본 연구에서는 20 대 ∼ 40 대 한국 여성을 대상으로 피부 수분량, 피부 멜라닌, 피부 붉은기, 피부비틀림 탄력을 측정하여 기초 피부 특성 데이터를 수집하고, 이를 나이와 상관성 분석을 진행하여 피부 지수를 만들고 이에 기반 하여 4 개의 군집으로 분류하여 그 특성을 확인하였다. 그 후 시제품 2 종을 2 주간 사용하여 피부 수분량, 피부 붉은기, 피부 각질량 감소에 대한 개선 효과를 확인한 후, 해당 시험자 중 피부 특성시험에 참여했던 피험자들을 대상으로 어느 군집에서 어떤 제품이 더 효과적이었는지 분석하였다. 이를 통해 피부 지수와 군집분석결과를 제품 효능평가에 반영하여 맞춤형 화장품 시장에 대비할 수 있는 가능성을 확인하였다. In this study, basic skin characteristics data were collected by measuring skin hydration, skin melanin, skin redness, and skin torsion elasticity from Korean women in from 20’s to 40’s ages, and then, age and correlation analysis were conducted. This was used to create a skin index, and cluster analysis was performed to classify the groups into 4 clusters, and the skin characteristics of each cluster were confirmed. Then, two prototypes were used for two weeks to confirm the improvement effect on skin moisture, skin redness, and skin dead mass reduction, and then analyzed which product was more effective in which cluster of subjects participated in the skin characteristics test. As a result of the study, the possibility of preparing for the customized cosmetics market was confirmed by applying the skin index and cluster analysis results to product efficacy evaluation.